Karakteristik Morfologi dan Anatomi Jahe (Zingiber Officinale) Berdasarkan Perbedaan Ketinggian Tempat - Mareta Widiya; Ria Dwi Jayati; Hevi Fitriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the differences in the morphology and anatomy of ginger plants based on differences in altitude, and to make a booklet resulting from the morphological and anatomical characteristics of ginger for morphology and plant anatomy courses. This research method is a qualitative research method. Data collection techniques in this study through observation, interviews, characterization techniques, document review, and questionnaires or questionnaires. Data analysis techniques with quantitative descriptive and descriptive analysis. The results of the study showed that there were differences in the morphological and anatomical characteristics of ginger based on differences in the height of the place. Ginger in Selupu Rejang District has a high stomata density. Ginger is more suitable for planting in the lowlands with high temperatures, low humidity. The compilation and manufacture of morphology and plant anatomy course booklets were declared valid with very decent qualifications with a percentage of 86.2%. Conclusion, there are differences in the morphological and anatomical characteristics of the ginger plant based on the height of the place, while the booklets that are made have proper and valid qualifications to be used as material for plant morphology and anatomy courses. Keywords: anatomy, ginger, characteristics, morphology